2015
DOI: 10.1051/0004-6361/201425535
|View full text |Cite
|
Sign up to set email alerts
|

Emission-line-selected galaxies atz= 0.6–2 in GOODS South: Stellar masses, SFRs, and large-scale structure

Abstract: We have obtained deep NIR narrow and broad (J and Y) band imaging data of the GOODS-South field. The narrow band filter is centered at 1060 nm corresponding to redshifts z = 0.62, 1.15, 1.85 for the strong emission lines Hα, [Oiii]/Hβ and [Oii], respectively. From those data we extract a well defined sample (M(AB) = 24.8 in the narrow band) of objects with large emission line equivalent widths in the narrow band. Via SED fits to published broad band data we identify which of the three lines we have detected an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 85 publications
2
11
0
Order By: Relevance
“…For example, most existing approaches rely on the adoption of a rigid physical model (e.g., analytic, two-parameter star formation histories combined with a standard dust attenuation curve and the assumption that all stars in a galaxy have the same metallicity) to describe galaxy SEDs (e.g. Bolzonella et al 2010;Wuyts et al 2011;Ilbert et al 2013;Muzzin et al 2013;Hernán-Caballero et al 2013;Bauer et al 2013;Lundgren et al 2014;Mortlock et al 2015;Kawinwanichakij et al 2016;Kochiashvili et al 2015). Even with the inclusion of superimposed bursts of star formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For example, most existing approaches rely on the adoption of a rigid physical model (e.g., analytic, two-parameter star formation histories combined with a standard dust attenuation curve and the assumption that all stars in a galaxy have the same metallicity) to describe galaxy SEDs (e.g. Bolzonella et al 2010;Wuyts et al 2011;Ilbert et al 2013;Muzzin et al 2013;Hernán-Caballero et al 2013;Bauer et al 2013;Lundgren et al 2014;Mortlock et al 2015;Kawinwanichakij et al 2016;Kochiashvili et al 2015). Even with the inclusion of superimposed bursts of star formation (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For GOODS-S, the survey took a total integration time in the NB of 31.9 h and 3.3 h in the J-band. Kochiashvili et al (2015) has recently published a study focused on the main sequence of starformation using ELGs at z = 0.6−2 within this large programme data. In our work, we make use of these deep GOODS-S images to extract a sample of Hα emitters at z ∼ 0.62.…”
Section: Data and Sample Selectionmentioning
confidence: 99%
“…There is still some debate over whether submm galaxies lie above the main sequence, or simply form its high-mass end. This debate is not primarily concerned with the form of the main sequence, as most studies agree that, at high redshifts, the main sequence continues to extend to high stellar masses with SFR ∝ M x * , where x is in the range 0.75-1.0 (Karim et al 2011;Speagle et al 2014;Renzini & Peng 2015;Schreiber et al 2015;Koprowski et al 2016;Dunlop et al 2017) with no evidence of any break as has been suggested at lower redshifts (Oliver et al 2010;Whitaker et al 2014;Ilbert et al 2015;Lee et al 2015;Tomczak et al 2016), or from galaxy surveys based purely on optical data (Kochiashvili et al 2015;Tasca et al 2015). Based on morphological decomposition at low redshifts this break was shown to disappear when only disc (not bulge) stellar mass was used (Abramson et al 2014).…”
mentioning
confidence: 99%